Cottage Resort Simalem Park (Traditionalism) - Firman Eddy; Rini Oktarine S (Talenta Publisher, 2019)
Tourism will be producing foreign exchange in Indonesia. Indonesia has a tourism appeal that manifests itself in traditional homes and village. In promoting Indonesian tourism to foreign countries, traditional architecture is a better choice, but fewer relics of traditional building art are worth a visit. Sumatera is an ethnically diverse island. Sumatera has become a tourist attraction that is often visited by foreign tourist. Resort attractions are becoming tourist attractions and lodging that is frequented by foreign tourist. There are several problems, namely how to realize the planning and design of resort cottages by considering traditional architecture and having planning standards that need to consider based on comparative studies carried out, then how to process the appearance of the building to fit the atmosphere in Taman Simalem Resort. With the aim of the design is to realize the concept of designing Resort Cottages and supporting facilities such as restaurants and spas by applying the principles of Traditional architecture. The design method used in the object design includes two aspects, namely the approach to the design theme, location, and environmental studies.